Bauhinia bauhinioides cruzipain inhibitor reduces endothelial proliferation and induces an increase of the intracellular Ca2+ concentration - BİLGİN, MEHMET; Bilgin, MEHMET; NEUHOF, Christiane; DOERR, Oliver; BENSCHEID, Utz; ANDRADE, Sheila S.; MOST, Astrid; ABDALLAH, Yaser; PARAHULEVA, Mariana; GUENDUEZ, Dursun; OLIVA, Maria L.; ERDOGAN, Ali (My University, 2010)
Proteinase inhibitors, isolated from different types of Bauhinia, have an effect on apoptosis, angiogenesis and inflammation. The Bauhinia bauhinioides cruzipain inhibitor (BbCI) is a Kunitz-type inhibitor and inactivates the cysteine proteinases cruzipain and cruzain from Trypanosoma cruzi. Cruzipain and tissue kallikrein have similar biochemical properties, e.g. the proteolytic cleavage of the kininogen precursor of lys-bradykinin. Tissue kallikrein stimulation in endothelial cells causes migration and capillary tube formation. The aim of this study was to examine whether the antiproliferative effect of BbCI is dependent on changes of the intracellular calcium concentration and membrane hyperpolarization. Endothelial cells were isolated from human umbilical cord veins (HUVEC). For proliferation experiments, HUVEC were incubated with BbCI (10-100 mu mol/L) for 48 h. The proliferation was detected by cell counting with a Neubauer chamber. The effect of BbCI (10-100 mu M) on the membrane potential was measured with the fluorescence dye DiBAC(4)(3) and the effect on [Ca+2] (i) with the fluorescence probe Fluo-3 AM. The change of the fluorescence intensity was determined with a GENios plate reader (Tecan). The experiments showed that BbCI (10-100 mu mol/L) reduces the endothelial cell proliferation significantly in a concentration-dependent manner with a maximum effect at 100 mu mol/L (35.1 +/- 1.8% as compared to control (p a parts per thousand currency signaEuro parts per thousand 0.05; n = 45)). As compared to the control, the addition of BbCI (100 mu mol/L) caused a significant increase of systolic Ca2+ of 28.4 +/- 5.0% after 30 min incubation. HUVEC treatment with BbCI (100 mu mol/L) showed a weak but significant decrease of the membrane potential of 9.5 +/- 0.9% as compared to control (p a parts per thousand currency signaEuro parts per thousand 0.05; n = 80). BbCI influenced significantly the endothelial proliferation, the intracellular Ca2+ concentration and the membrane potential.